Comparisons Between Histology and Optical Coherence Tomography Angiography of the Periarterial Capillary-Free Zone - Balaratnasingam, Chandrakumar; An, Dong; Sakurada, Yoichi; Lee, Cecilia S.; Lee, Aaron Y.; McAllister, Ian L.; Freund, K. Bailey; Sarunic, Marinko; Yu, Dao-Yi (American journal of ophthalmology, 2018)
To use the capillary-free zone along retinal arteries, a physiologic area of superficial avascularization, as an anatomic paradigm to investigate the reliability of optical coherence tomography angiography (OCTA) for visualizing the deep retinal circulation. Validity analysis and laboratory investigation. Five normal human donor eyes (mean age 69.8 years) were perfusion-labeled with endothelial antibodies and the capillary networks of the perifovea were visualized using confocal scanning laser microscopy. Regions of the capillary-free zone along the retinal artery were imaged using OCTA in 16 normal subjects (age range 24–51 years). Then, 3 × 3-mm scans were acquired using the RTVue XR Avanti (ver. 2016.1.0.26; Optovue, Inc, Fremont, California, USA), PLEX Elite 9000 (ver. 1.5.0.15909; Zeiss Meditec, Inc, Dublin, California, USA), Heidelberg Spectralis OCT2 (Family acquisition module 6.7.21.0; Heidelberg Engineering, Heidelberg, Germany), and DRI-OCT Triton (Ver. 1.1.1; Topcon Corp, Tokyo, Japan). Images of the superficial plexus, deep vascular plexus, and a slab containing all vascular plexuses were generated using manufacturer-recommended default settings. Comparisons between histology and OCTA were performed. Histologic analysis revealed that the capillary-free zone along the retinal artery was confined to the plane of the superficial capillary plexus and did not include the intermediate and deep capillary plexuses. Images derived from OCTA instruments demonstrated a prominent capillary-free zone along the retinal artery in slabs of the superficial plexus, deep plexus, and all capillary plexuses. The number of deep retinal capillaries seen in the capillary-free zone was significantly greater on histology than on OCTA (P < .001). Using the capillary-free zone as an anatomic paradigm, we show that the deep vascular beds of the retina are not completely visualized using OCTA. This may be a limitation of current OCTA techniques.